The use of Hajj fund for investment purpose: a maqashid sharia approach - Singgih Muheramtohadi (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2019)
Purpose - Hajj financial use The Hajj is an obligation for Muslims who can carry out. Over time, the number of people who perform Hajj is increasing, but the quota is minimal. It raises new problems; one of them is the problem of the financial management of Hajj. The financial of Hajj accumulates and inflation occurs every year. One of the solutions to the financial problem in Hajj is to invest in a productive field. The purpose of this paper is to find out the Islamic scholars’ consideration of the justification of using Hajj fund and investing it in productive fields.Method - This research is conducted through a qualitative descriptive approach.Result - All Islamic organizations in Indonesia, especially MUI (Majelis Ulama Indonesia/ Indonesian Ulama Council), justify the Hajj financial use.Implication - The result can be used by society as information and consideration regarding Hajj and the mechanism of financial management in religious prayers administered by the government.Originality - This research study the recent existence of investment purposes in Hajj fund management.